2012
DOI: 10.1177/0361684312451842
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behavior and Sexual Assault Among Ethnically Diverse Women

Abstract: Sexual assault is associated with a number of health risk behaviors in women. It has been hypothesized that these risk behaviors, such as hazardous drinking, may represent women's attempts to cope with psychological distress, such as symptoms of depression and anxiety. However, extant research has failed to evaluate these relationships among ethnic minority samples or identify the mechanisms responsible for this association. The current study examined sexual assault history and two health risk behaviors (hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 69 publications
2
38
0
1
Order By: Relevance
“…Several previous studies have observed the mediating role of depression and anxiety on the relationship between childhood abuse, risky sexual behavior, and revictimization (Gidycz et al, 1993; Littleton et al, 2013; Orcutt et al, 2005). Much of the revictimization literature has focused on the mediating role of posttraumatic stress disorder (PTSD) symptoms in the path from childhood abuse to ASA (e.g., Fortier et al, 2009; Risser, Hetzel-Riggen, Thomsen, & McCanne, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have observed the mediating role of depression and anxiety on the relationship between childhood abuse, risky sexual behavior, and revictimization (Gidycz et al, 1993; Littleton et al, 2013; Orcutt et al, 2005). Much of the revictimization literature has focused on the mediating role of posttraumatic stress disorder (PTSD) symptoms in the path from childhood abuse to ASA (e.g., Fortier et al, 2009; Risser, Hetzel-Riggen, Thomsen, & McCanne, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have examined the impact of varied distress symptoms on sex-related coping and revictimization risk. Specifically, Littleton et al (2013) found that symptoms of depression and anxiety mediated the relation between sexual assault history and use of SRNA among a sample of ethnically diverse college women. Similarly, Orcutt et al (2005) found that psychological distress (i.e., depression, anxiety, and hostility) and use of SRNA partially mediated the relation between CSA and prospective ASA in a sample of community women.…”
Section: Outcomes Following Victimization: Distress and Strategies Fomentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that a history of CSA may be associated with a greater likelihood of engaging in sexual risk behavior in adulthood (Meston, Heiman, & Trapnell, 1999;Parillo, Freeman, Collier, & Young, 2001;Testa, VanZile-Tamson, & Livingston, 2005;Van Bruggen, Runtz, & Kadlec, 2006). However, it should be noted that this relationship has not always been found (e.g., Hamburger et al, 2004;Littleton, Radecki Breitkopf, & Berenson, 2007;van Roode et al, 2009;Watson, Matheny, Gagne, Brack, & Ancis, 2013). Overall, the literature supports that having a CSA history is associated with engaging in sexual risk behavior during adolescence and may also be associated with the persistence of sexual risk behavior into adulthood.…”
mentioning
confidence: 99%
“…There have also been limited studies that show how sexual attitudes affect unwanted sex from an attachment perspective (Feeney & Noller, 2004;Sprecher, 2013). According to Littleton, Grills-Taquechel, Buck, Rosman, and Dodd (2013), casual sexual interactions that involve more sexual partners may increase risk of sexual assault because of the increased ''likelihood of encountering a sexually assaultive partner'' (p. 8). As well, in many of the existing studies focused on attachment and unwanted sex, the participants were all female.…”
Section: Attachment Theory and Unwanted Sexmentioning
confidence: 99%